Effects of occupational exposure to lead on blood pressure and neurocognitive functions - Nadia Tigha-Bouaziz (Arterial Hypertension)
BACKGROUND: The objective was to calculate the prevalence of high blood pressure among lead-exposed welders and study its role in altering neurocognitive functions. MATERIAL AND METHODS: This cross-sectional analytical epidemiological study included 30 lead-exposed welders and 30 controls. Hypertension was assessed through a medical questionnaire and blood pressure measurement. Neurocognitive functions were evaluated using Euroquest, Profile of Mood States (POMS), and neurocognitive tests. We used T and Z tests, chi-square, relative risk, and logistic regression. RESULTS: The subjects were men with an average age of 42 years. The prevalence of hypertension was higher in the exposed group compared to the non-exposed (10% vs. 6.6%). The onset age of hypertension was 28 years for weldersvs. 38 years for controls. The risk of hypertension increased by 1.5 times, correlating with years of lead exposure (RR = 2). Adjustment for confounding factors confirmed the relationship with the duration of exposure. Hypertensive individuals showed more symptoms in Euroquest and POMS, with a significant decline in performance in neurobehavioral tests such as Digit Symbol and Digit span digit back visual retention (p < 0.05). CONCLUSION: Long-term exposure to lead was found to increase blood pressure and constitute a risk factor for cardiovascular diseases. Lead exposure impairs cognitive functions, especially with increased blood pressure.